HIV Pandemic, Medical Brain Drain, and Economic Development in Sub-Saharan Africa - Bhargava, Alok (World Bank, 2012)
Country-level longitudinal data at three-year intervals over 1990–2004 are used to analyze the factors affecting emigration of physicians from Sub-Saharan countries and the effects of this medical brain drain on life expectancy and number of deaths due to AIDS. Data are compiled on emigrating African physicians from 16 receiving Organisation for Economic Co-operation and Development (OECD) countries. A comprehensive longitudinal database is developed by merging the medical brain drain variables with recent data on HIV prevalence rates, public health expenditures, physicians' wages, and economic and demographic variables. A triangular system of equations is estimated in a random effects framework using five time observations for medical brain drain rates, life expectancy, and number of deaths due to AIDS, taking into account the interdependence of these variables. Lower wages and higher HIV prevalence rates are strongly associated with the brain drain of physicians from Sub-Saharan African to OECD countries. In countries in which the HIV prevalence rate exceeds 3 percent, a doubling of the medical brain drain rate is associated with a 20 percent increase in adult deaths from AIDS; medical brain drain does not appear to affect life expectancy. These findings underscore the need to improve economic conditions for physicians in order to retain physicians in Sub-Saharan Africa, especially as antiretroviral treatment becomes more widely available.